ANALYSIS OF FACTORS CAUSING JABODETABEK COMMUTER TRAIN DELAY - Prasadja Ricardianto; Eko Purnomo; Erna Widodo; Masjraul Hidayat (ABNUS Publisher, 2021)
The goal to be achieved through this research is to identify the factors that cause delays in the commuter train journey across Bogor-Manggarai Jakarta. The research question is why there is a delay in the journey of the Jakarta Bogor, Depok, Tangerang, Bekasi Commuter Train crossing Bogor-Manggarai. This study uses the Analytic Hierarchy Process to analyze timeliness. With the number of informants taken as many as 12 informants consisting of five people from regulators, five people from operators, one expert in the field of railways and users of commuter train of Jakarta Bogor, Depok, Tangerang, Bekasi. From the measurement results, it was found that the Jakarta, Bogor, Depok, Tangerang, Bekasi Commuter Train was still experiencing delays, due to follow-ups and cross-changes in the operation pattern of the Jakarta Bogor, Depok, Tangerang, Bekasi Commuter Train which was still mixed with long-distance and freight trains, the construction of the Manggarai station as part of the Double Double Track project, the signaling system at the station. Manggarai also underwent changes and there were speed restrictions at Manggarai Station. Recommendations are to complete the construction of the Manggarai and Jatinegara stations which are useful for separating inter-city and urban rail travel, updating the signaling system on the crossing between Bogor Station-Manggarai Station and City Station which is now 30 years old, handling and improving level crossings with coordinate with related units.